Enhanced transesterification reaction using chromium-doped calcium oxide-based catalyst supported on alumina and its specification of biodiesel - Sulaiman N.F.; Leong Y.W.; Lee S.L.; Toemen S.; Bakar W.A.W.A. (Elsevier Ltd, 2024)
A new modification with an active substance, chromium-doped calcium oxide-based catalyst supported on alumina (Cr-Ca/?-Al2O3), was synthesized by the wetness impregnation method in the transesterification of refined waste cooking oil. 10Cr-90Ca/?-Al2O3 catalyst calcined at 700 C was successful in achieving a maximum of 86.6% of biodiesel production under optimum parameters (reaction temperature of 65 C, catalyst loading of 6 wt%, oil-to-methanol of 1:18 mol ratio, and reaction time of three hours). The optimization using 10Cr-90Ca/?-Al2O3 catalyzed reaction was subsequently verified by response surface methodology. Based on the R2 value of 0.9977, the regression equation fits well and explains a significant response to the observed variability. The analyses from X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM) indicated that the active species existence in 10Cr-90Ca/?-Al2O3 catalysts was Ca2+ and Cr3+ played important roles in this catalytic transesterification reaction for biodiesel production. The 10Cr-90Ca/?-Al2O3 catalyst calcined at 700 C had the smallest crystallite size measured at 9.4 nm (Al2O3), 8.9 nm (CaO), and 17.9 nm (Cr2O3). The TGA-DTA data validated the temperature of 700 C was considered suitable for synthesized 10Cr-90Ca/?-Al2O3 catalyst. The fuel qualities of synthesized biodiesel under ideal process conditions meet ASTM D6751 and EN 14214 standards. 2023 Elsevier Ltd